GFAPδ: A Promising Biomarker and Therapeutic Target in Glioblastoma - Radu, Roxana; Petrescu, George E. D.; Gorgan, Radu M.; Brehar, Felix M. (Frontiers in Oncology, 2022)
GFAPδ, the delta isoform of the glial fibrillary acidic protein, is mainly expressed in the subventricular zone of the brain, together with other neural stem cell markers like nestin. The authors of this paper were among the first that described in detail the expression of GFAPδ and its correlation with malignancy and invasiveness in cerebral astrocytoma. Later, several papers confirmed these findings, showing that the alternative splice variant GFAPδ is overexpressed in glioblastoma (CNS WHO grade 4) compared with lower grade gliomas. Other studies suggested that a high GFAPδ/α ratio is associated with a more malignant and invasive behavior of glioma cells. Moreover, the changing of GFAPδ/α ratio affects the expression of high-malignant genes. It is now suggested that discriminating between predominant GFAP isoforms, GFAPδ or GFAPα, is useful for assessing the malignancy state of astrocytoma, and may even contribute to the classification of gliomas. Therefore, the purpose of this paper is to review the literature with emphasize on the role of GFAPδ as a potential biomarker, and as a possible therapeutic target in glioblastoma.